Age-specific association between non-HDL-C and arterial stiffness in the Chinese population - Wang, Jie; Miao, Rujia; Chen, Zhiheng; Wang, Jiangang; Yuan, Hong; Li, Jing; Huang, Zheng (Frontiers in Cardiovascular Medicine, 2022)
Background: While some epidemiological studies have found correlations between non-high-density lipoprotein cholesterol (non-HDL-C) and arterial stiffness, there are still exist controversial and age-stratified analysis are scarce yet. Methods: All individuals in this study were recruited in the Third Xiangya Hospital of Central South University from 2012 to 2016. Arterial stiffness was defined as brachial-ankle pulse wave velocity (baPWV)≥1400 cm/s. Association between non-HDL-C and arterial stiffness were explored using Cox proportional-hazards model. We also conducted subanalysis stratified by age. Furthermore, restricted cubic splines were used to model exposure-response relationships in cohort sample. Results: This cohort study included 7276 participants without arterial stiffness at baseline. Over a median follow-up of 1.78 years (IQR, 1.03-2.49), 1669 participants have identified with incident arterial stiffness. In multivariable-adjusted analyses, higher non-HDL-C concentration was associated with incident arterial stiffness with an adjusted hazard ratio (HR) of 1.09 (95% confidence interval [CI], 1.02-1.17) per 1 mmol/l increase. Compared with the lowest tertile, the HR for arterial stiffness with respect to the highest tertile of non-HDL-C was 1.26 (95% CI, 1.07-1.48). The results were similar in the analysis of young participants (age <60 years). Conclusion: Our study identified that non-HDL-C as a potential risk factor of arterial stiffness, especially for younger. The clinical benefits of decreasing non-HDL-C concentration should be further considered in the future.